THE ROLE OF TECHNOLOGY IN THE FORMATION OF MOTIVATION IN TEACHING ENGLISH TO STUDENTS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In today's rapidly evolving educational landscape, technology has become a powerful tool that shapes the ways students learn and stay motivated. Especially in language learning, like English, technology serves as a catalyst that enhances engagement and motivation. Traditional methods of teaching often fail to address the diverse needs of students, while technology provides a range of options that cater to different learning styles and preferences. By making use of multimedia, gamified experiences, and collaborative tools, educators can create an environment where students are more engaged and motivated to learn.Moreover, the integration of technology allows for a more personalized approach to education. Students can work at their own pace, revisiting challenging concepts and advancing more quickly through areas they already understand. This autonomy contributes significantly to motivation, as learners feel more in control of their education. The ability to interact with real-life content, participate in virtual simulations, and collaborate online makes learning more relevant and enjoyable. Ultimately,technology not only supports the academic aspect of learning but also fosters a lifelong passion for language acquisition.